Perbedaan Pengaruh Transcutaneus Electrical Nerve Stimulation Dan William Flexion Exercise Dengan Transcutaneus Electrical Nerve Stimulation Dan Core Stability Terhadap Pengurangan Nyeri Pada Penderita Spondylosis Lumbal - PURBA, RISMAIDAH; HARTONO, ADI; PUSPA SARI, TENGKU LUSI (Universitas Teknokrat Indonesia, 2024)
Lumbar spondylosis is low back pain caused by degeneration of the disc, facet joint in the lumbar, resulting in an emphasis on the intervertebral foramen which will cause osteophytes where this causes irritation and will cause pain. The purpose of this study was to determine the difference in the effect of Transcutaneus Electrical NerveStimulation and William Flexion Exercise with Transcutaneus Electrical NerveStimulation and Core Stability in reducing pain in patients with Lumbar Spondylosis. Randomized two group pre-test post-test design, with the first group of 10 patients with the intervention of Transcutaneus Electrical Nerve Stimulation and William Flexion Exercise and the second group of 10 people with the intervention of Transcutaneus Electrical Nerve Stimulation and Core Stability conducted for 6 weeks with Visual AnaloqueScale measuring instruments. Treatment group I with Transcutaneus Electrical Nerve Stimulation and William Flexion Exercise is p=0.004 (p0.05) which means there is an effect of treatment in reducing pain, as well as treatment group II with Transcutaneus Electrical Nerve Stimulation and Core Stability is p=0.004 (p0.05) which means there is an effect of treatment in reducing pain. While the comparison between the first treatment and the second treatment is p=0.014 (p0.05) which means there is a difference in the effect of Transcutaneus Electrical Nerve Stimulation and William Flexion Exercise with Transcutaneus Electrical Nerve Stimulation and Core Stability in reducing pain in patients with Lumbar Spondylosis. Transcutaneus Electrical Nerve Stimulation and William Flexion Exercise are better than Transcutaneus Electrical Nerve Stimulation and Core Stability to reduce pain in patients with Lumbar Spondylosis.